A Review of Optimization Approach to Power Flow Tracing in a Deregulated Power System - Tijani, M. A.; Adepoju, G. A.; Hamzat, K. A.; Sanusi, M. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Power Flow Tracing (PFT) is known to be the best method in the allocation of charges to users of transmission systems, generators and loads, in a deregulated environment. The optimization approach to PFT produced better results than other methods because it considers the physical power flow results and electrical constraints of the system. A brief review of the optimal power flow concept, PFT techniques, and the deterministic and non-deterministic optimization methods applied to PFT are presented. The paper also highlighted the future trends of hybrid optimization approach to PFT. It is recommended that more research work should be directed on the hybrid optimization methods to solve PFT problems.